2011
DOI: 10.1007/s12070-011-0367-7
|View full text |Cite
|
Sign up to set email alerts
|

Proptosis: The ENT Surgeon’s Perspective

Abstract: Proptosis is one of the commonest clinical manifestations of pathology involving orbit. Aim of this study is to evaluate causes of proptosis secondary to nasal and paranasal sinus pathology. Prospective study over 2 years. 44 cases of proptosis secondary to nasal and para nasal sinus pathologies studied. There were 63.6% males and 33.4% of females with peak age incidence between 41 and 50 years. Commonest cause of proptosis in our study is malignancy of nose and paranasal sinuses, of which squamous cell carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 5 publications
2
12
0
1
Order By: Relevance
“…The lowest incidence was noted in in the group of patients aged 0-15 years old, accounting for 8 cases (13%). These data aresimilar tothe ones presented in the study by Venugopal et al, 6 in which the incidence of proptosis secondary to ENT disorders increased with advancing age.…”
Section: Demographicssupporting
confidence: 88%
“…The lowest incidence was noted in in the group of patients aged 0-15 years old, accounting for 8 cases (13%). These data aresimilar tothe ones presented in the study by Venugopal et al, 6 in which the incidence of proptosis secondary to ENT disorders increased with advancing age.…”
Section: Demographicssupporting
confidence: 88%
“…In the study by Sajid et al, age range of the patients obtained also broad enough that from the age of 1-75 years with the largest age group is 31-40 years (26.67%). 6 In another study by Venugopal M et al, 10 maximum cases were in the age group of 41-50 years (20.5%). If we observed tendency of age according to each disease, sinusitis are most common in the younger age group 0-20 years, sinonasal tumours in the age group 41-50 years and mucocele group age 0-10 years.…”
Section: Discussionmentioning
confidence: 88%
“…Another study by Yousry and Malik et al also found the number of male patients were more common than women by a ratio of respectively 3.5:1 and 2:1. Another study by Rahman A et al 3 reported male and female ratio of 1.6:1, while Venugopal M et al 10 had ratio of 1.9:1, but Sajid et al get the opposite result with the ratio of men compared to women is 1:4. [5][6][7] From the 32 patients with paranasal sinus disease, 13 (40.6%) of them were due to sinusitis, mostly of maxillary sinus origin (10 cases), 6 (18.75%) cases were of sinonasal malignancy, all of which were histopathologically confirmed to be squamous cell carcinoma of maxillary sinus, 6 (18.75%) cases were of mucoceles from frontoethmoidal origin, 4 (12.50%) cases were of fibrous dysplasia of maxillary sinus, 2 (6.25%) case was of schwannoma of frontal sinus origin and 1 (3.12%) case of Langerhans cell histiocytosis of maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] These 2 patients with orbital cellulitis were young males and concur with the findings of Pjerin Radovani et al, [8], [10] Among the benign neoplastic lesion, fibrous dysplasia was the only lesion noted when compared to Venugopal et al, who state that angiofibroma was the most common benign tumor causing proptosis followed by inverted papilloma, chondroma of ethmoid, ossifying fibroma and fibrous histiocytoma. [7] Among malignant tumours, squamous cell carcinoma was found to be the most common histological type. This is in agreement with studies by Frazell E. L. et al, Venugopal et al and several other previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with studies by Frazell E. L. et al, Venugopal et al and several other previous studies. [11,7,6,12] All the cases of malignancy underwent total maxillectomy with radiotherapy and chemotherapy wherever indicated. The patient with angiofibroma underwent radiation therapy.…”
Section: Discussionmentioning
confidence: 99%